Banana Bunchy Top Virus (BBTV) Delimiting Survey in Tanzania: Phase 1 Survey Summary Report - Mahuku, G.; Kumar, P.L. (International Institute of Tropical Agriculture, 2023)
A severe outbreak of banana bunchy top virus (BBTV), responsible for the bunchy top disease of bananas, was reported in Tanzania in 2021. BBTV spreads through infected planting material and by the aphid Pentalonia nigronervosa, which is widespread in all banana production areas. Delimiting surveys were conducted between May and July 2023 in 85 districts in 15 regions, which represent all the major banana production areas in the country. The virus was detected in 22 districts in 10 regions: Dar es Salaam, Dodoma, Morogoro, Mbye, Katavi, Geita, Kigoma, Kilimanjaro, Mwanza, and Pwani. The virus was not detected in surveyed sites in Arusha, Kagera, Manyara, Mara, and Tanga regions. In many farms, virus infection led to a 90-100% production loss. The drivers of BBTV spread include the lack of awareness that impeded early detection, lack of capacity for surveillance, diagnostics, eradication, and access to virus-free planting materials. A multi-stakeholder alliance has been established to coordinate surveillance and early detection and implement actions to curb virus spread and recover banana production in Tanzania.